FARBER DISEASE - DISEASE DESCRIPTION WITH CASE REPORTS - I. A. Chikova; N. V. Buchinskaya; М. М. Kostik; V. V. Avramenko; O. L. Krasnogorskaya; R. A. Nasirov; T. Levade; V. G. Chasnyk ("Paediatrician" Publishers LLC, 2014)
Farber disease (lipogranulomatosis, OMIM 228000) - is extremely rare autosomal-recessive disorder from group of lysosomal storage disorders, due to deficiency of acid ceramidase activity enzyme. Farber disease has a lot of clinical masques and resembles to different inflammatory disorders, such as juvenile arthritis, chronic urticaria, larynx papillomatosis and others. Most effective therapeutic method is bone marrow transplantation, which leads to minimization of disabling and improve quality of life. Currently a medication for enzyme replacement therapy of Farber disease is produced and it is under the clinical trials. We describe clinical course of two patients with different types of Farber disease. First case - 10 years old boy with II-III type of disease, and second - with fatal outcome in the age of 4 years 3 months of boy with I (classical) type of Farber disease.